IMPROVEMENT OF SOIL BY NAILING - Ameer Abdulridha Ajmi Alali (Western European Studies, 2024)
The basic principle of soil nailing is to embed closely spaced steel bars, or "Nails," into a slope in order to reinforce and fortify the current round as construction proceeds in a "top-down" fashion. This process creates a stable component that is fortified and able to cling to the earth behind it. The soil nailing technique is used to sustain new, extremely steep cuttings because it has the advantage of strengthening the slope with large earthworks to allow construction access and operating in conjunction with widely used retaining systems. In this article, we have examined several nail factors, including nail length, angle of inclination, spacing, and placement. The height and angle of the slope dictate the optimal nail length. The optimal nail angle has been found to be between 10 and 25 degrees below the horizon, while the slope angle also plays a role. It was shown that the most improvement in F.S. resulted from nail spacing of one millimetre.
Keywords: improvement of soil; Soil nailing; Stability